Profile of Anti-Diphtheria Toxoid Immunoglobulin G among Pre-School Children in the Senen District, Jakarta, Indonesia - Santi, Theresia; Jo, Juandy; Prayitno, Ari; Munasir, Zakiudin; Hegar, Badriul (Writing Center IMERI FMUI, 2023)
Background: Diphtheria is a re-emerging disease in Indonesia that can be prevented by vaccination. This study evaluates the anti-diphtheria toxoid immunoglobulin G levels among healthy children aged 6 – 7 years old who had not received the second booster immunization for Diphtheria, Tetanus, and Pertussis (DTP) commonly administered at 5 – 7 years old. Methods: This cross-sectional study was conducted in the Senen district of Jakarta, Indonesia. All subjects had been vaccinated with three doses of immunization for DTP during the first year of life, and subsequently classified into a group of children who received the first booster immunization of DTP at 18 – 24 months old and who had not received it yet. Antibody against Diphtheria toxoids within the sera samples was assessed by commercial Anti-Diphtheria toxoid IgG Enzyme-Linked Immunosorbent Assay and classified in four groups: no protection (< 0.01 IU/ml), uncertain (0.01 – 0.09 IU/ml), full protection (0.10 – 1 IU/ml) and long-term protection (>1 IU/ml). Results: Eighty-nine children were included in this study; only 71 subjects (79.7%) had received the first DTP booster at 18–24 months old. The specific humoral immunity against diphtheria was observed among 57 children (64%). Notably, among the 89 subjects, only two subjects not receiving the first DTP booster still had antibody protection for diphtheria (p=0.001, OR 27.5, 95% CI: 5.71 – 132.42). Conclusion: The first diphtheria booster vaccination at 18 – 24 months old is crucial to protect pre-school children against diphtheria.